The hidden cost of minimum quality standards: Evidence from the U.S. clothes washer market - Sébastien Houde; Tobias Wekhof (ETH Zurich, CER-ETH - Center of Economic Research, 2025)
Minimum standard regulations for durables have long been suspected of having hidden costs: quality improvements in the regulated dimension reduce quality in other dimensions. We substantiate this claim for the U.S. clothes washer market, which has become a notorious example of the hidden cost phenomenon due to a 2004 energy efficiency requirement. We find that overall quality increased from 2001 to 2011, and these gains were primarily driven by improvements in energy efficiency. Quality in the non-energy dimensions declined or remained constant after the major standard change. These hidden costs were, however, compensated by energy-efficiency improvements.
Keywords: Q48; Q55; L51; L68; D12; 330; Minimum Quality Standard; Hidden Cost; Energy Efficiency Regulations; Appliance Market; Ex Post Analysis